Re-energizing health literacy in Wales: a testbed for health, education and prosperity for all - Emily Marchant (Health Promotion International, 2024)
A growing body of evidence demonstrates the importance of enhancing health literacy for improved health outcomes, self-reported health, lower health services use and disease prevention. Importantly, improving health literacy has great potential to reduce health inequities and inequalities. The World Health Organization (WHO) has identified health literacy as a global priority, viewing it as a right and a fundamental competency necessary to function within modern society. Building health literacy foundations should begin in early childhood, including focus within educational frameworks and school curricula. The WHO advocate for governments to embed it as an explicit goal. In response, it has received significant international policy and strategy focus, in addition to the development of country-level action plans. In Wales, UK, it was identified as a priority in 2010, but despite wider developments spanning health and social care, well-being, economy and education policy, growth in health literacy has stalled since. Optimizing health literacy would act as an indirect enabler to a range of Welsh policies and strategies. A promising avenue for strengthening the health literacy of current and future generations is through ongoing significant national education reforms and the introduction of the new Curriculum for Wales. One of four overarching purposes of this curriculum is healthy, confident individuals, and health and well-being constitutes one of six statutory curriculum areas. Tracking the impact of this on children and young people’s health literacy offers opportunities for Wales to model and gain traction as a national-scale health literacy policy testbed. This requires re-energizing health literacy as a national priority.